2021
DOI: 10.1111/aos.15020
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and association of visual impairment with myopic maculopathy across age groups among highly myopic eyes – based on the new classification system (ATN)

Abstract: Purpose To investigate the percentages and risk factors for visual impairment (VI) across age groups in a highly myopic cohort with a wide range of age (18–93 years). Methods A total of 2099 eyes (1220 participants) were enrolled. All participants underwent detailed ocular examinations. Myopic maculopathy (MM) was assessed as myopic atrophy maculopathy (MAM), myopic traction maculopathy (MTM) or myopic neovascular maculopathy (MNM) based on the ATN system. Results Most participants younger than 50 years had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The risk of MM is higher in persons of older age, regardless of myopia severity and AL, which places MM as an age-related degenerative disease [ 26 – 28 ]. This is consistent with our findings, reporting an increase of prevalence with higher age (OR = 1.084 per year).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of MM is higher in persons of older age, regardless of myopia severity and AL, which places MM as an age-related degenerative disease [ 26 – 28 ]. This is consistent with our findings, reporting an increase of prevalence with higher age (OR = 1.084 per year).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MM was the leading cause of bilateral visual impairment and blindness [ 2 – 4 , 28 ]. Our study mirrored this link between MM and visual impairment and blindness, with 81.7% (76/93) of participants with MM having a present visual acuity classified as visual impairment or blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Details about this study are available in our previous publication. 18 The protocol was approved by the Ethics Committee of Shanghai General People's Hospital, Shanghai Jiao Tong University School of Medicine, in compliance with the tenets of the Declaration of Helsinki. Written informed consent forms were signed by all participants.…”
Section: Methodsmentioning
confidence: 99%
“…It was conducted on Chinese adults (≥ 18 years old) who volunteered to participate after reading our study description and an open invitation to become participants. Details about SHMSA and SGHMS have been described in our previous study [24,25]. The exclusion criteria were presence of secondary myopia, intraocular pressure (IOP) > 21 mmHg, corneal opacity, severe cataract, glaucoma, fundus lesions that were unrelated to myopia (e.g., age-related macular degeneration, diabetic retinopathy, and optic neuropathy), systemic diseases with ocular involvement, history of eye surgery (except cataract surgery), and poor-quality images (image quality < 60).…”
Section: Study Subjectsmentioning
confidence: 99%